Flexible Platform Oriented: Unipolar‐Type Hybrid Dual‐Channel Scalable Field‐Effect Phototransistors Array Based on Tellurium Nanowires and Tellurium‐Film with Highly Linear Photoresponsivity. (24th February 2022) - Naqi, Muhammad; Choi, Kyung Hwan; Cho, Yongin; Rho, Hyun Yeol; Cho, Haewon; Pujar, Pavan; liu, Na; Kim, Hyun‐Suk; Choi, Jae‐Young; Kim, Sunkook
Abstract: Here, a novel method is introduced to synthesize the uniform hybrid structure of tellurium nanowires (TeNWs) and tellurium‐film (Te‐film) for flexible field‐effect transistor (FET) array device to exhibit excellent electrical, mechanical, and optical performance. To fabricate such a device, all the processes are performed at low temperatures (< 100 °C) with easy processing methods. The uniformity of the hybrid structure of TeNWs/Te‐film is confirmed using scanning electron microscopy (SEM) and Raman spectroscopy with a comparison of the bare TeNWs‐film. Electrical properties of the TeNWs/Te‐based FET device exhibits high mobility of 5.35 cm 2 V −1 s −1 and on/off ratio of >10 4 along with stable and uniform results of the transistor array device, which consists of 50 devices. The optical properties show highly linear photodetection behavior in terms of threshold voltage shift, responsivity, sensitivity, photocurrent, detectivity, and time‐domain behavior. Also, the various stability tests are performed to confirm the consistency of the device in terms of positive bias stress, negative bias stress, positive bias illumination stress, long‐term stability response (up to 60 days), mechanical bending stress, and the results reveal a constant and consistent behavior of the device, which can be attributed to enable wide range applications in the field of electronics devices. Abstract : Herein, a novel method is introduced to synthesize and fabricate the uniform hybrid structure of tellurium nanowires (TeNWs) and tellurium‐film (Te‐film) for flexible field‐effect transistor array device to exhibit excellent electrical, mechanical, and optical performance. The stability analysis tests reveal a highly stable and consistent behavior. The proposed device with stable performance can enable new opportunities to broaden the application in the optoelectronics field.